2023
DOI: 10.1111/dom.15369
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 reduces STAT3 activation and causes impaired mitochondrial quality control in diabetic cardiomyopathy

Lu Zhou,
Wating Su,
Yafeng Wang
et al.

Abstract: AimsTo investigate the role of FOXO1 in STAT3 activation and mitochondrial quality control in the diabetic heart.MethodsType 1 diabetes mellitus (T1DM) was induced in rats by a single intraperitoneal injection of 60 mg · kg−1 streptozotocin (STZ), while type 2 diabetes mellitus (T2DM) was induced in rats with a high‐fat diet through intraperitoneal injection of 35 mg · kg−1 STZ. Primary neonatal mouse cardiomyocytes and H9c2 cells were exposed to low glucose (5.5 mM) or high glucose (HG; 30 mM) with or without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Foxo1, as the target of sirt1, plays an important role in mitophagy. 37 In order to explore its possible mechanism in SAH, we detected the level of foxo1 and ac-foxo1. The results shown that inhibiting the expression of sirt1 increased the level of ac-foxo1, thereby reducing the level of mitophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Foxo1, as the target of sirt1, plays an important role in mitophagy. 37 In order to explore its possible mechanism in SAH, we detected the level of foxo1 and ac-foxo1. The results shown that inhibiting the expression of sirt1 increased the level of ac-foxo1, thereby reducing the level of mitophagy.…”
Section: Discussionmentioning
confidence: 99%